TELOMERES AND TELOMERASE COMPLEX. THE MAIN CLINICAL MANIFESTATION OF GENETIC MALFUNCTIONING - О. М. Drapkina; R. N. Shepel (Кардиоваскулярная терапия и профилактика)
Telomeres and telomerase complex have got be known by scientists not long ago. At the current moment there quite large data on this topic collected. The row of diseases has been described that are caused by "shelterin" genes mutations, genes of telomerase complex subunits genes associated with telomeres. There is direct correlation of telomere length decrease and the risk of variety of diseases, including cardiovascular disorders. The review concerns on history, structure andfunction of telomeres and telomerase complex; the diseases are described that occur due to the damage of the structures mentioned.